2020
DOI: 10.1021/acsnano.0c07128
|View full text |Cite
|
Sign up to set email alerts
|

Properties of DNA- and Protein-Scaffolded Lipid Nanodiscs

Abstract: The properties of natural lipid bilayers are vital to the regulation of many membrane proteins. Scaffolded nanodiscs provide an in vitro lipid bilayer platform to host membrane proteins in an environment that approximates native lipid bilayers. However, the properties of scaffold-enclosed bilayers may depart significantly from those of bulk cellular membranes. Therefore, to improve the usefulness of nanodiscs it is essential to understand the properties of lipids restricted by scaffolds. We used computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…Using eq , we determined the width of such a boundary layer to be ≈20 Å, which corresponds to a corona of ≈2.5 DMPC lipids wide. This provides experimental verification of MD simulations, reporting that the lipid packing is high in the center of nanodiscs and gradually drops the closer the lipids are to the surrounding MSP. , Ideally, the choice of the MSP for nanodisc preparation should be made by making sure to use a MSP large enough that the membrane protein is unlikely to be located in the region of the lipid bilayer corresponding to the boundary lipid layer. In this regard, it is interesting to note that the Escherichia coli lipid transporter MsbA has up to a 100-fold tighter binding to ATP but a slower hydrolysis rate in large nanodiscs (MSP1E3D1) compared to that in smaller nanodiscs (MSP1D1) .…”
Section: Resultsmentioning
confidence: 74%
“…Using eq , we determined the width of such a boundary layer to be ≈20 Å, which corresponds to a corona of ≈2.5 DMPC lipids wide. This provides experimental verification of MD simulations, reporting that the lipid packing is high in the center of nanodiscs and gradually drops the closer the lipids are to the surrounding MSP. , Ideally, the choice of the MSP for nanodisc preparation should be made by making sure to use a MSP large enough that the membrane protein is unlikely to be located in the region of the lipid bilayer corresponding to the boundary lipid layer. In this regard, it is interesting to note that the Escherichia coli lipid transporter MsbA has up to a 100-fold tighter binding to ATP but a slower hydrolysis rate in large nanodiscs (MSP1E3D1) compared to that in smaller nanodiscs (MSP1D1) .…”
Section: Resultsmentioning
confidence: 74%
“…Coarse-grained MD simulations found that the number of charge-neutralized DNA nucleotides can be as important as the length of the hydrophobic alkyl chains in stabilizing a patch of a lipid bilayer encircled by a DNA origami nanodisc. 36 Another all-atom MD study of membrane-spanning nanopores 37 found the density of the charges along the DNA backbone to affect the transmembrane transport of water and ions. While computational exploration of larger DNA−lipid constructs is currently possible using the allatom MD approach, 38 multiresolution simulation approaches 39 are expected to bring out the best combination of computational efficiency and molecular realism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to the hydrophobicity of individual charge-neutralized nucleotides, their density within a DNA duplex can also influence the binding and insertion of DNA into a lipid bilayer membrane. Coarse-grained MD simulations found that the number of charge-neutralized DNA nucleotides can be as important as the length of the hydrophobic alkyl chains in stabilizing a patch of a lipid bilayer encircled by a DNA origami nanodisc . Another all-atom MD study of membrane-spanning nanopores found the density of the charges along the DNA backbone to affect the transmembrane transport of water and ions.…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular dynamics (MD) studies have been performed on NDs and related lipid particles, analyzing their self-assembly and structural properties. , However, setting up simulation systems of NDs is not a trivial task. In 2015, Siuda and Tieleman published a potential protocol for constructing NDs in silico , based on the crystal structure with PDB ID 1AV1 .…”
Section: Introductionmentioning
confidence: 99%